Principles of Physical Education of Children in the Works of Jędrzej Śniadecki - Aistis Žalnora (Acta Medico-Historica Rigensia, 2019)
The article is devoted to the concept of physical education of children that were presented in papers of Jędrzej Śniadecki (1768–1838), a famous Polish-Lithuanian doctor, anthropologist, biologist, chemist, and philosopher. The study revealed that the works of J. Śniadecki were partly characteristic of the Enlightenment period. The main goal of Śniadecki’s papers was to educate society in order to fight with superstitions and negative habits that were widely spread in the working class as well as the upper class. He focused on preventive measures that would help to maintain good physical and mental health of a child, family and society. Śniadecki’s attitude included some Romanticist features. He believed that the modern way of living was dangerous for human health because of numerous social factors that changed the primary perfection, purity and natural powers of the human body. As an opposition to the modern lifestyle he puts natural- istic way of living. However, Śniadecki was also one of the first anthropologists in Lithuania and Poland. His works were the first attempts to find correlations between numerous factors such as nutrition, heredity and development of the human body. Moreover, Śniadecki could be referred to as one of the pioneers in didactics. His insights related to the different teaching methods applied to the pupils’ age and sex remain relevant until now.